2013
DOI: 10.1021/am402097j
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Behaviors in Three-Dimensional Collagen-Hyaluronan Composite Hydrogels

Abstract: Glioblastoma multiforme (GBM) tumors, which arise from glia in the central nervous system (CNS), are one of the most deadly forms of human cancer with a median survival time of ~1 year. Their high infiltrative capacity makes them extremely difficult to treat, and even with aggressive multimodal clinical therapies, outcomes are dismal. To improve understanding of cell migration in these tumors, three-dimensional (3D) multicomponent composite hydrogels consisting of collagen and hyaluronic acid, or hyaluronan (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 64 publications
6
127
0
Order By: Relevance
“…Primary cells from glioma patient tumor material exposed to increasing concentrations of HA responded with rounded morphology and reduced migration, suggesting that HA concentrations may affect glioma cell behavior. [62] Consistently, addition of HA to porous chitosan scaffolds [63] or to artificial hydrogels [64] increased the expression of stem cell markers and VEGF and HIF-1, respectively. However, the finding that increasing matrix stiffness -by adding agarose to a collagen I matrix -blocks glioma invasiveness, [19] suggested that stiffness alone and independent of ligand binding acted as a critical determinant for primary brain tumor cell function.…”
Section: The Impact Of the Embedding Matrix On The Behavior Of The Tumentioning
confidence: 85%
“…Primary cells from glioma patient tumor material exposed to increasing concentrations of HA responded with rounded morphology and reduced migration, suggesting that HA concentrations may affect glioma cell behavior. [62] Consistently, addition of HA to porous chitosan scaffolds [63] or to artificial hydrogels [64] increased the expression of stem cell markers and VEGF and HIF-1, respectively. However, the finding that increasing matrix stiffness -by adding agarose to a collagen I matrix -blocks glioma invasiveness, [19] suggested that stiffness alone and independent of ligand binding acted as a critical determinant for primary brain tumor cell function.…”
Section: The Impact Of the Embedding Matrix On The Behavior Of The Tumentioning
confidence: 85%
“…Rao et al used composite hydrogels comprising mixtures of type I collagen and thiolated hyaluronic acid to examine the effects of ECM composition on primary human glioblastoma-derived cell motility. [61] They found that higher concentrations of hyaluronic acid correlated with a slower migration speed and more rounded cell morphology, as well as a higher elastic modulus of the gels. [61] The Harley group has utilized hydrogels comprising a combination GelMA, acrylated PEG, and methacrylated hyaluronic acid crosslinked via radical-initiated chain polymerization.…”
Section: Biomaterials For 3d Cell Biology Prospective Articlementioning
confidence: 97%
“…[61] They found that higher concentrations of hyaluronic acid correlated with a slower migration speed and more rounded cell morphology, as well as a higher elastic modulus of the gels. [61] The Harley group has utilized hydrogels comprising a combination GelMA, acrylated PEG, and methacrylated hyaluronic acid crosslinked via radical-initiated chain polymerization. [62][63][64] In one study, they found that increasing the relative amount of hyaluronic acid in the gel induced U87 glioblastoma cells to increase expression of genes associated with malignancy, including the angiogenic factor VEGF and the hypoxia marker HIF-1.…”
Section: Biomaterials For 3d Cell Biology Prospective Articlementioning
confidence: 97%
“…Therefore, to investigate the role of HA in GBM invasion, the HA is chemically modified so that it is cross-linked. Chemically modified forms of HA hydrogels include thiolated HA (Rao et al, 2013a), methacrylated HA (Ananthanarayanan et al, 2011;Kim and Kumar, 2014), and mixtures with GelMA . GBM cells are strongly influenced by the HA concentration and show increased invasion via CD44-mediated HA adhesion (Kim and Kumar, 2014).…”
Section: Matrices To Mimic the Ecm Componentsmentioning
confidence: 99%
“…Physical blending with other cross-linkable hydrogels, such as collagen, is another means of incorporating HA components into ECM-mimetic model system. By creating interpenetrating polymer networks with HA solution and collagen gels, HA-rich matrices can be created (Yang et al, 2011;Rao et al, 2013a;Cha et al, 2016). Within this HA-rich matric, GBM develops highly proliferative, invasive phenotypes (Cha et al, 2016).…”
Section: Matrices To Mimic the Ecm Componentsmentioning
confidence: 99%